البنية الحجاجية في اعتذاريات النابغة الذبياني - سقني, جحيدر, حميدة عفاف (جامعة الوادي university of eloued, 2017)
تناول هذا البحث أحد أهم القضايا اللغوية في اللغة العربية , ألا و هو الحجاج و بالتحديد في اعتذاريات النابغة الذبياني, وقد حاول هذا البحث الإجابة عن الإشكالية الآتية : ماهي البنية التي اتخذها النابغة الذبياني في بناء اعتذارياته ؟و هل تلك البنية حققت العملية الإقناعية ؟ وتهدف هذه الدراسة إلى الوقوف على أهمية البنية الحجاجية في اعتذاريات النابغة الذبياني و بيان دورها في تحقيق الإقناع للملك النعمان بن المنذر . وقد انتهجنا المنهج الوصفي و خاصة في عرض بنية و خصائص النص الحجاجي , أما التحليل فقد استخدمناه في الجانب التطبيقي من الموضوع . توصلنا إلى نتائج أهمها : أن الاعتذاريات سيطرت عليها حجج طرائق الاتصال و ذلك راجع لقوة الحجج الاتصالية في توصيل ما يريد النابغة الذبياني لتعبير عليه , وتصوير ما يريده لإقناع الملك النعمان بن المنذر. Résumé: L'objet de cette recherche se penche sur l’argumentation dans ¨les excuses de Nabigha Dybiani ¨ qui est l' un des cas linguistiques les plus importants dans la langue arale. Dans cette ,nous essyons de répondre a' la problématique suivante : ¨Quelle structure Nabigha Dhylyani a-t-il choisi pour écrire(élaborer) ses excuses? Cette structure a-t- elle renforce' l’acte de convaincre? Cette étude a principalement pour objectif de montrer l'importance de la structure argumentative dans "Les excuses de N.Dhylyani et son rôle dans la réalisation de la persuasion du roi Naman Ibnu – EL-Mound-her. Pour présenter la structure et les caractéristiques du texte argumentatif ,nous avons emprunté le dexriptif . Quant à l'analyse, nous l'avons utilisé dans le côté pratique du sujet . Les résultats que nous déduits montrent que "Les Excuses" sont dominées par l'argument communicatif qui permet à N. Dhylyani de s'exprimer et de concevoir ce qu' il voudrait pour convaincre le roi Nàmàn ibnou –EL-Moundher. Abstract: This research tackled one of the most important linguistic issues in the Arabic language, namely, the pilgrims, specifically in the apologies of the Nabegh Al-Zubayani. This research has attempted to answer the following problem: What is the structure taken by Al-Nabihi in building his apologies? The aim of this study is to find out the importance of the structure of the pilgrims in the apologies of the Nabeans and to explain their role in achieving the persuasion of King Al-Nu'man bin Al-Mundhir. We have followed the descriptive approach, especially in the presentation of the structure and characteristics of the text of the pilgrims, and the analysis we used on the practical side of the subject. We have reached the most important results: that the apologies dominated by the arguments of the methods of communication and this is due to the strength of the communicative arguments in the delivery of what he wants Alnbghp to express it, and portray what he wants to convince King Noman bin Mundhir.
Keywords: الحجاج – البنية الحجاجية – الاعتذاريات; Pèlerins - Structure orbitalis - Alaatmariaat; Pilgrims - Pilgrimage - Apologies